Commentary on Singapore - Gillian Koh (World Scientific series in finance, 2024)
This volume provides a collection of commentaries on Singapore's political leadership, governance, and foreign policy. Edited by Gillian Koh, it compiles analyses from scholars and practitioners that explore key developments and challenges in Singapore's political landscape and international relations.